2007
DOI: 10.1016/j.jacc.2007.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Unrestricted Use of Drug-Eluting Stents Compared With Bare-Metal Stents in Routine Clinical Practice

Abstract: The generalized use of DES resulted in better outcomes than BMS, with fewer clinically driven revascularization procedures and similar rates of death and MI at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 30 publications
3
54
0
1
Order By: Relevance
“…Indeed, more than half of all DES implants are performed for "off-label" or "unproven" indications. [7][8][9] These use patterns, coupled with emerging safety concerns, have led to substantial interest in comparative effectiveness studies of DESs versus bare metal stents (BMSs) in routine clinical practice. 10 -12 These studies, based on observational data, have generally confirmed the benefits of DESs on clinical restenosis and the need for repeat revascularization that were seen in the original clinical trials.…”
Section: Editorial See P 581mentioning
confidence: 99%
“…Indeed, more than half of all DES implants are performed for "off-label" or "unproven" indications. [7][8][9] These use patterns, coupled with emerging safety concerns, have led to substantial interest in comparative effectiveness studies of DESs versus bare metal stents (BMSs) in routine clinical practice. 10 -12 These studies, based on observational data, have generally confirmed the benefits of DESs on clinical restenosis and the need for repeat revascularization that were seen in the original clinical trials.…”
Section: Editorial See P 581mentioning
confidence: 99%
“…In the National Heart, Lung, and Blood Institute (NHLBI) Dynamic Percutaneous Coronary Intervention (PCI) Registry, the prevalence of diabetes increased from 23% in 1997 to 1999 to 31% in 2004. 2,3 Similarly, in the Nationwide Inpatient Sample, the percentage of patients undergoing coronary artery bypass graft (CABG) having diabetes increased from 16.7% in 1988 to 1990 to 33.9% from 2003 to 2005. 4 Patients with type 2 diabetes mellitus (T2DM), compared with those without diabetes, have a greater and more extensive atherosclerotic burden associated with impaired compensatory remodeling of the arterial wall.…”
mentioning
confidence: 99%
“…Numerous randomized trials and observational studies have demonstrated significant reductions in clinical and angiographic restenosis compared with bare metal stents (BMS), [1][2][3][4][5] leading to widespread use of DES in both approved and "off-label" applications. 5,6 Nonetheless, several critical questions regarding DES remain unresolved.…”
mentioning
confidence: 99%